Eksperimen Model Pembelajaran Problem Based Learning (Pbl) Berbasis Assessment For Learning (Afl) Ditinjau Dari Kemampuan Penalaran Matematis (Pada Siswa Kelas VIII SMP Negeri 1 Ngemplak Tahun Pelajaran 2015/2016) - Erica Amanda Nugraheni, Valensia, Rita P. Khotimah, S.Si., M.Sc, M. Noor Kholid, S.Pd., M.Pd (2015)
This study aims to determine: (1) Effect of learning model Problem Based Learning-based Assessment for Learning and Problem Based Learning for mathematics achievement, (2) Effects of mathematical reasoning abilities for mathematics achievement, (3) Effects of interaction between learning models and mathematical reasoning abilities for mathematics achievement. Research conducted a quasi-experimental research, while the population is taken that all eighth grade students of SMP Negeri 1 Ngemplak the school year 2015 / 2016. The sampling technique used is random sampling with a sample 34 students of class VIII B as experimental class and 33 students of class VIII A as control class. The technique used to collect data were documentation and test. The data analysis technique used is two-way analysis of variance with a cell is not the same as the level of significance of 5%. Results of this study as follows. (1) There is effect of learning model PBL based AfL and PBL for mathematics achievement, (2) There is effects of mathematical reasoning abilities for mathematics achievement, (3) There is no interaction effect between learning models and mathematical reasoning abilities mathematics achievement.